Violence in general practice: Perceptions of cause and implications for safety - Magin, Parker (College of Family Physicians of Canada, 2008)
OBJECTIVE: To explore GPs’ opinions about the causes of occupational violence in general practice. DESIGN: A cross-sectional qualitative study. SETTING: Three urban divisions of general practice in New South Wales, Australia. PARTICIPANTS: A total of 172 GPs: 18 GPs participated in focus group discussions and a further 154 provided written responses. METHOD: Purposive sampling was used to recruit GPs to participate in focus groups. Discussions were audiotaped and transcribed; each transcript was separately coded by all members of the research team. Focus groups were conducted until thematic saturation was achieved. Further qualitative data were obtained by offering GPs the opportunity, during completion of a written questionnaire sent to all GPs practising in the 3 urban divisions, to provide additional comments regarding their experiences and perceptions of violence. A modified grounded-theory approach, employing thematic analysis of the focus group transcripts and written responses from the questionnaires, was used. MAIN FINDINGS: All focus group participants and 75% of questionnaire respondents had experienced episodes of violence during their general practice careers. Key themes that emerged in data analysis were used to construct a schema of participating GPs’ perceptions of the causes of occupational violence. Elements in the schema include underlying causes, proximate causes, and GP vulnerability. Perhaps the most noteworthy findings within this structure were the emergent constructs—culture of fear, “naïve” practice culture, and GP vulnerability. To date these themes have not been evident in general practice literature on this topic. CONCLUSION: An understanding of GPs’ perceptions regarding the causes of violence will be useful in planning general practice service provision and promoting GP safety.